EVALUATING THE IMPACT OF PRICING STRATEGIES ON ORGANIZATIONAL PERFORMANCE OF SOME SELECTED BAKERIES IN GOMBE - BALA, ABUBAKAR; IBRAHIM, USMAN YAHYA; LADAN, KAMILAT SHEHU; HASSAN, AISHA ADAMU (Kashere Journal of Management Sciences, 2025)
This research examines the impact of three pricing strategies; cost-plus pricing, customer value-based pricing, and competitive pricing, on the performance of specific bakeries in Gombe State, Nigeria. Anchored in the Resource-Based View, Customer Value Theory, and Porter’s Competitive Advantage Theory, the study offers a theoretical framework for comprehending how pricing decisions influence performance outcomes. A descriptive survey approach was utilized, and data were gathered using a structured questionnaire distributed to 142 respondents selected through a proportionate stratified random sampling method. The data were examined utilizing SPSS version 20, incorporating descriptive statistics, Pearson’s correlation, and simple linear regression. The results indicated that all three pricing models positively and significantly influence organizational performance. Cost-plus pricing bolstered financial stability, customer value-based pricing fostered customer loyalty and revenue growth, and competitive pricing augmented market share and customer acquisition. The research finds that implementing a hybrid pricing model enhances both financial and non-financial outcomes. It enhances the body of knowledge by associating pricing strategies with organizational performance in the context of small and medium-sized firms within Nigeria’s bakery sector.